SISTEM PENDUKUNG KEPUTUSAN PENERIMA DANA DESA DENGAN MENGGUNAKAN METODE PROMETHEE DI KECAMATAN GODEAN KABUPATEN SLEMAN - Arif Budiman; Adi Prasetyo; M Hamzah (Universitas Janabadra, 2019)
Decision support systems for village funds were used to assist the head of the Community and Village Empowerment Agency in deciding the priorities of recipients of village funds. Village funds can be used for the purposes of financing governance, development and community empowerment. The method used in designing and making this application is the PROMETHEE method for ranking the priorities of village fund recipients in sleman district. Village funds are funds originating from the APBN intended for villages that are transferred through the APBD and used to finance the administration, implementation, development, community development, and empowerment of village communities. The purpose of this study is to develop a decision support system that can be used by regional heads as a tool to assist in the selection of priority recipients of village funds to be given funds. Based on calculations using the Promethee method, the results obtained ranking with the highest net flow value of 0.292 namely A4 so that the village of Sidokarto will be the priority of the recipient of village funds in the district Sleman Keywords : Village Funds, Decision Support System, Promethee